Optical and Digital Techniques for Information Security - Javidi, Bahram (Advanced Sciences and Technologies for Security Applications, 2005)
Optical and Digital Techniques for Information Security is the first book in a series focusing on Advanced Sciences and Technologies for Security Applications. This book encompases the results of research investigation and technologies used to secure, verify, recognize, track, and authenticate objects and information from theft, counterfeiting, and manipulation by unauthorized persons and agencies. This Information Security book will draw on the diverse expertise in optical sciences and engineering, digital image processing, imaging systems, information processing, computer based information systems, sensors, detectors, and biometrics to report innovative technologies that can be applied to information security issues. The Advanced Sciences and Technologies for Security Applications series focuses on research monographs in the areas of: -Recognition and identification (including optical imaging, biometrics, authentication, verification, and smart surveillance systems) -Biological and chemical threat detection (including biosensors, aerosols, materials detection and forensics) -Secure information systems (including encryption, and optical and photonic systems). The series is intended to give an overview at the hightest research level at the frontier of research in the physical sciences.